Pengaruh Persepsi Wajib Pajak UMKM Atas Undang-Undang HPP, Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM - Herti Diana Hutapea; Amran Manurung; Kristiani Sihotang (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The low level of MSME taxpayer compliance is one of the causes of not optimal tax revenue in Indonesia. The total MSME actors reached 64.2 million while the number of MSME actors registered as taxpayers was only 2.31 million or 3.6% of MSMEs registered as taxpayers was only 15%, which means that the level of MSME taxpayer compliance is still low. So in order to increase taxpayer compliance, one of the efforts made by the Government together with the DPR was the issuance of the Law on the Harmonization of Tax Regulations (UU HPP) no.7 years 2021. The purpose of this study was to determine the effect of MSME taxpayers' perceptions of the HPP law and to determine the effect of tax socialization on taxpayer compliance. This research data is primary data by providing questionnaires directly and online using the Google form to MSMEs in North Sumatra. The sampling technique used purposive sampling method. And the hypothesis test used is multiple regression analysis. The results show that the perceptions of MSME taxpayer on the HPP Law have a positive and significant effect on MSME Taxpayer compliance. MSME taxpayers who have a positive perception of the HPP Law accept the decision so that MSME taxpayer compliance is also positive. Meanwhile, tax socialization has no effect on MSME taxpayer compliance. This is because MSME taxpayers follow the tax socialization invitation from Direktorat Jendaral pajak (DJP), and most of the research samples are DJP assisted MSMEs, so the socialization is only a formality, the material obtained is only listened to and MSME taxpayers are more enthusiastic about participating in training related to development his skills.It is hoped that this research can be used as a source of information for MSME taxpayers in making decisions on taxpayer perceptions of the HPP Law which will affect the level of taxpayer compliance and the development of taxation theory.